Histoire de l'occupation allemande en Belgique - Jouret, Georges; Masson, F. (Mons : La Province, 1927)
Bibliotheek Camille Huysmans
Dedicator: Jouret, Georges, dedicatee: Huysmans, Camille
Frans
Monografie
Keywords: Wereldoorlog 1